СРAВНИТЕЛЬНЫЙ AНAЛИЗ ЭНЕРГЕТИЧЕСКОЙ ПОЛИТИКИ КAЗAХСТAНA И ИРAНA В СФЕРЕ ВИЭ - Гaбдуллин, К. Т.; Шупaновa, Р. Э. (Journal of Oriental Studies, 2018)
In this article, the energy policy of Iran and Kazakhstan in the sphere of RES is compared. The results of the research can be used in political science connected with the analysis of the energy policy of the national security of Iran and Kazakhstan, and can be used in further development in the framework of political knowledge about energy policy; to improve the efficiency of the energy policy in the area of renewable energy in Kazakhstan, based on the experience of Iran. The methodology of the study is based on an interdisciplinary approach that encompasses economic and political science. In the course of the research, scientific principles and methods of analysis, synthesis, comparison, as well as a comparativehistorical method were used, which as a result helped to reveal the general and specific features of the research subject, prospects and qualitative characteristics of its development.